Analisis Efektivitas Metode Pelaksanaan Pemasangan Pipa HDPE pada Sistem Distribusi Air Minum PDAM di Kecamatan Bunder Manyar, Kabupaten Gresik - Muhammad Sofyan; Yurnalisdel Yurnalisdel; Suhudi Suhudi (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2025)
The construction of drinking water pipeline networks is a critical component of a sustainable Drinking Water Supply System (SPAM). The success of pipeline construction is heavily influenced by the appropriate selection of construction methods tailored to on-site conditions. The Umbulan Sub-Distribution Center (Sub DC) Bunder–Manyar SPAM project in Gresik Regency is a strategic project utilizing High-Density Polyethylene (HDPE) pipes with large nominal diameters and a significant route length. Diverse on-site conditions, such as open areas, road crossings, and river crossings, require the application of appropriate construction methods to ensure the work proceeds effectively and efficiently. This study aims to analyze the construction methods for HDPE DN pipelines applied in this project, analyze the costs and duration of the work, and evaluate project progress based on actual on-site conditions. The research method used is a descriptive approach combining qualitative and quantitative methods. Data was obtained through direct field observations as well as a review of the Cost Estimate (RAB), work schedule, and project progress reports. The research results show that the open-cut method is predominantly used in areas with open terrain and easy access, while the Horizontal Directional Drilling (HDD) method is applied in areas crossing roads and rivers. Based on the analysis of costs and implementation time, the application of methods appropriate to site conditions can improve work efficiency and support the achievement of project progress in accordance with the plan. Thus, the selection of the appropriate implementation method plays a crucial role in the success of drinking water pipeline network projects.